Method to locate the polar cap boundary in the nightside ionosphere and application to a substorm event - Aikio, A. T.; Pitkänen, T.; Kozlovsky, A.; Amm, O. (Annales Geophysicae, 2006)
In this paper we describe a new method to be used for the polar cap boundary (PCB) determination in the nightside ionosphere by using the EISCAT Svalbard radar (ESR) field-aligned measurements by the 42-m antenna and southward directed low-elevation measurements by the ESR 32 m antenna or northward directed low-elevation measurements by the EISCAT VHF radar at Tromsø. The method is based on increased electron temperature (Te) caused by precipitating particles on closed field lines. Since the Svalbard field-aligned measurement provides the reference polar cap Te height profile, the method can be utilised only when the PCB is located between Svalbard and the mainland. Comparison with the Polar UVI images shows that the radar-based method is generally in agreement with the PAE (poleward auroral emission) boundary from Polar UVI. The new technique to map the polar cap boundary was applied to a substorm event on 6 November 2002. Simultaneous measurements by the MIRACLE magnetometers enabled us to put the PCB location in the framework of ionospheric electrojets. During the substorm growth phase, the polar cap expands and the region of the westward electrojet shifts gradually more apart from the PCB. The substorm onset takes place deep within the region of closed magnetic field region, separated by about 6–7° in latitude from the PCB in the ionosphere. We interpret the observations in the framework of the near-Earth neutral line (NENL) model of substorms. After the substorm onset, the reconnection at the NENL reaches within 3 min the open-closed field line boundary and then the PCB moves poleward together with the poleward boundary of the substorm current wedge. The poleward expansion occurs in the form of individual bursts, which are separated by 2–10 min, indicating that the reconnection in the magnetotail neutral line is impulsive. The poleward expansions of the PCB are followed by latitude dispersed intensifications in the westward electrojet with high latitudes affected first and lower latitudes later. We suggest that reconnection bursts energize plasma and produce enhanced flows toward the Earth. While drifting earthward, part of the plasma population precipitates to the ionosphere producing latitude-dispersed enhancements in the WEJ.